A CHOICE OF THE SHORTEST OF THE ALTERNATIVE COMPRESSED BLOCKS OF THE DYNAMIC HUFFMAN’S CODES IN THE FORMAT OF PNG - Shport’ko, Alexander (International Journal of Computing, 2014)
In the article the algorithm of generation of the alternative compressed blocks of dynamic Huffman’s codes for every block of data, choice of the shortest compressed block of alternative and iterative diminishing of its size for the improvement of the compression of images in the format of PNG is offered. The methods of the estimation of the size of block of Huffman’s codes according to the absolute frequencies of its elements are examined in details. The fragment of programs outlaying the language of C, which allows exactly to determine the size of the compressed block by principle of generation of dynamic Huffman’s codes and separate working of small frequencies of elements, using for this purpose on the average not more time, than for the close estimation of size with the use of entroping. As experiments show, realization of the offered algorithm, allows to improve the indexes of the compression of the majority of images in the format of PNG in 2 – 6 %.